OUR EXPERIENCE WITH DACARBAZINE IN THE TREATMENT OF PATIENTS WITH INOPERABLE SKIN MELANOMA - Deyan Davidov (Peytchinski Publishing, 2016)
Objective: The standard treatment for inoperable skin melanoma is chemotherapy. The aim of this study was to explore the efficacy and safety of therapy with dacarbazine in patients with advanced melanoma. Methods: Twenty- seven consecutive patients with inoperable stage III or IV skin melanoma were treated with chemotherapy. Treatment schedule consists of dacarbazine 150 mg/ m2 days 1- 5 administered every 3- 4 weeks. Results: Overall response rate was 14,8% with four partial remissions. The main toxicity were neutropenia and vomitus. Conclusions: These data confirm that advanced skin melanoma is resistant of chemotherapy with dacarbazine.